Brand Switching Behavior Influenced by Product Attributes and Variety Seeking with Consumer Trust as a Mediating Variable - Dematria Pringgabayu; Agus Rahayu; Heny Hendrayati; Ayuningtyas Yuli Hapsari (Jurnal Multidisiplin Madani, 2023)
The movement of cellular operators to other brands is of course a picture for the company. Therefore companies must be able to increase product innovation both from all aspects of the product attributes offered, such as service quality and pricing that meet consumer desires or needs for product variations. This study aims to determine whether brand switching behavior is really influenced by product attributes and also variety seeking, and researchers also use the consumer trust variable as a mediator. The research method used was a descriptive and explanatory survey with a total sample of 384 people. The results of the study prove that product attributes and variety seeking have a positive and significant influence in forming consumer trust, and consumer trust has a positive and significant effect in shaping brand switching behavior. It can be seen that this variable has the greatest test value so that it can be concluded that customer trust is a the biggest influence on brand switching on customers